Sensor development life cycle of embedded fiber bragg grating sensor for structural health monitoring - Ghorai, S.K.; Roy, Dipta Ranjan (Journal of Structural Engineering, 2024)
SHM (structural health monitoring) involves the development of an autonomous system for continuous monitoring, inspection and damage detection of structures with minimum involvement of labor. Recent research works has shown that fiber optic sensors¹ has several inherent advantages over conventional electrical, electro-mechanical or mechanical sensors because of its small size, light-weight, non-conductivity, fast response, resistance to corrosion, higher-temperature capability, immunity towards electromagnetic interference and ease of embedding into composite materials. Fiber Bragg grating (FBG) sensors, a special class of fiber-optic sensor, have distinct advantages over other available form of fiber optic sensors as well as non-fi ber optic sensor. It can serve both as the sensing element and the signal transmission medium. Moreover, because of its multiplexing capability and wavelength-encoded measurand (strain, temperature, pressure, humidity etc.) information it serves as a reliable source of remote SHM. In this work, we tried to give a complete methodology for designing and using an embedded FBG sensing system for quasi-static strain monitoring. In the process, we came up with a theoretical model, coined by us as SDLC (sensor development life cycle), which is capable of reducing the computational complexities for developing the sensing system. Simple flowcharts are used to represent our ideologies, and also to make it more useful and acceptable to any engineering domain (viz. civil, mechanical, aerospace etc.). A theoretical analysis for designing FBG, LPG (long period grating) and SFBG (superstructure fiber Bragg grating) using 2-mode coupling and higher-order mode coupling is also discussed here. A robust digital signal processing technique, to retrieve information about the measurands, from the sensor output signal is given by us.